Inflammatory biomarkers of neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios in 563 severe OSA patients before and after surgery - Chung-Wei Lin; Pei-Wen Lin; Li-Wen Chiu; Han-Tan Chai; Chun-Tuan Chang; Michael Friedman; Anna M. Salapatas; Sara Rahavi-Ezabadi; Hsin-Ching Lin (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Evidence has proved that high neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) were risk factors for cardiovascular comorbidities. The alterations of NLR and PLR following obstructive sleep apnea (OSA) treatment were under studied and thus should be investigated. This study aimed to evaluate the changes of inflammatory biomarkers including NLR and PLR in severe OSA patients after surgical interventions of the upper airway, and their relationships with improvements in polysomnographic (PSG) parameters. Methods This retrospective cohort study included 563 consecutive severe OSA patients at a tertiary academic medical center who received OSA surgery, as well as underwent pre- and post-operative polysomnographic (PSG) examinations and blood tests. The changes of major PSG estimates, NLR, and PLR before and at least 3 months after OSA surgery were analyzed using paired t-tests with subgroup analyses. Pearson’s correlations were performed to discover which PSG parameter contributed to the improvement of the values. Results After OSA surgery, the major PSG estimates, NLR and PLR dropped significantly in the overall population. In those with a higher preoperative NLR (pre-operative NLR≧3) and PLR (pre-operative PLR≧150), the mean (SD) difference of NLR (− 0.8 [1.6], 95% CI − 1.5 to − 0.2) and PLR (− 41.6 [40], 95% CI − 52.8 to − 30.5) were even more substantial. The changes of the “apnea, longest (r = 0.298, P = .037)” and “hypopnea, longest (r = 0.321, P = .026)” were found significantly related to the improvement of PLR. Conclusion NLR and PLR did significantly drop in severe OSA patients following OSA surgery, and this could be related to the alterations of sleep indices. The findings could possess clinical importance for severe OSA patients after OSA surgeries in reducing possible OSA-associated cardiovascular comorbidities.